GREEN CHEMISTRY - AN ECO-FRIENDLY ALTERNATIVE IN OBTAINING AG0 NANOPARTICLES - Alarcón, Hugo (2021)
Attentiveness in silver nanoparticles (AgNPs) is due to their optical, catalytic and antibacterial properties; which depend on its size, shape and colloidal stability. AgNPs can be obtained by chemical, physical and biological techniques; However, “Green Chemistry” approach promotes the development of research that does not include toxic substances or high-cost conditions in the synthesis of nanoparticles, an alternative is the use of extracts of plants, algae, fungi, bacteria and viruses as agents. reducers and stabilizers in the synthesis process. For this reason, this research employs ethanolic extracts of petals and leaves of Solanumgrandiflorum Ruiz & Pav to obtain AgNPs with a particle size less than 50 nm. Using UHPLCESI- Q-Orbitrap-MS-MS, the mayor secondary metabolites present in ethanolic extracts were identified, AgNPs were characterized by UV-Vis, FTIR, DLS and FE-SEM.